(untitled) (Discourse of Law and Administration, 2023)
The authors try to examine legal and political narratives regarding the pathway of Ukraine to the European Union. We feel the considerable support of Ukrainians (86% in favor of the European future). Also, we should trust our president, parliament, and government share the same values and desire the same destiny for our country. Therefore, they should fulfill urgent reforms necessary for every candidate country to join the European Union. The framework of successful reforms should include issues on guaranteeing the rule of law and respect for human rights and fundamental freedoms, protecting personal data, cooperating on migration, asylum, and border management, preventing and combating money laundering and terrorism financing, fighting against illicit drugs, and on precursors and psychotropic substances, combating and preventing criminal and illegal activities (corruption), etc.